Protestant social thought in Latin America - Bullón, H. Fernando (Regnum Books International, 2015)
This work is concerned with describing the bond of Protestant social thought to the processes of theorizing about development on Latin America, an aspect that has not received sufficient treatment in most recent literature. An assessment of the Protestant social thought is done not only to understand its own evolutive process, but as a product of and in contrast with the more specialized context of reflection on social and economic transformation and change, as is shown in the academic and practical-political debate at the continental level.